2008
DOI: 10.1021/jp073318n
|View full text |Cite
|
Sign up to set email alerts
|

Strong Two-Photon Absorption in Push−Pull Phthalocyanines:  Role of Resonance Enhancement and Permanent Dipole Moment Change upon Excitation

Abstract: We study near-IR two-photon absorption (2PA) spectra of nonsymmetric push-pull metal-free phthalocyanines, which are present in solution at room temperature as a mixture of two spectrally nonequivalent tautomers T1 and T2. Large 2PA cross sections, σ 2 ) (1-3) × 10 3 GM, are obtained in the excitation wavelength region λ ex ) 815-850 nm and are explained by ( 1) a new charge transfer state appearing in the one-photon absorption (1PA) spectrum of these compounds at 420-430 nm and (2) a strong resonance enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 67 publications
2
48
0
Order By: Relevance
“…The UC emission is a result of different excitation schemes: either two-photon absorption (TPA) in organic molecules, [7,8] quantum dots [1] or in proximity of metallic clusters. [9] Another well established technique is the sequential energy transfers (ETU) in rare earth ion-doped glasses.…”
Section: Introductionmentioning
confidence: 99%
“…The UC emission is a result of different excitation schemes: either two-photon absorption (TPA) in organic molecules, [7,8] quantum dots [1] or in proximity of metallic clusters. [9] Another well established technique is the sequential energy transfers (ETU) in rare earth ion-doped glasses.…”
Section: Introductionmentioning
confidence: 99%
“…So far, such measurements involving the higher-energy states, although possible, remain relatively difficult. We have found that in many practical situations a good quantitative agreement between the measured s 2 value and that calculated from perturbation theory can be achieved by considering few essential states [4,[26][27][28][29][30]. Fig.…”
Section: Theoretical Backgroundmentioning
confidence: 59%
“…The molecular 2PA cross-section, s 2 , may be expressed from quantum-mechanical perturbation theory as a function of transition dipole moments and permanent dipole moment differences between the states (sum-over-the-states model) [23][24][25]. We have recently shown that often in cases of practical interest good quantitative description is achieved already by accounting for two or three lower-energy states (few essential states model) [4,[26][27][28][29][30]. Here we focus on a special situation of the lowestenergy transition in dipolar chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only relatively few classes of NIR dyes that are readily available. These include the phthalocyanines, cyanine dyes and squaraine dyes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%